A review on development and application of self-healing thermal barrier composite coatings - Abuchenari, Aliasghar; Ghazanfari, Hadi; Siavashi, Mostafa; Sabetzadeh, Maryam; Talebi, Sajad; Karami Chemeh, Zahra; Jamavari, Ata (Journal of Composites and Compounds, 2020)
To improve the hot section metallic parts durability in advanced gas-turbine operating in power generation and aircraft, thermal barrier coating (TBCs) are extensively utilized to increase their lifetime. The reason for applying coatings on these components is the improvement of their physical properties, mechanical properties, and outer look. The self-repairing ability of materials is very promising due to expanding the service time of materials and it is also beneficial in terms of human safety and financial aspects. In this review article, structure, properties, limitations, and the modification approaches of TBCs were studied. In addition, self-healing agents for TBCs including SiC, MoSi2, TiC were introduced, which release their oxide by reaction with air and O2 that are able to heal the pores/cracks in the coatings. In this regard, their coating methods, mechanism, and applications in TBCs were reviewed.